2014
DOI: 10.1002/app.41333
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyHIPE/clay composites by using a reactive intercalant

Abstract: Porous polymer composites have been synthesized by polymerizing the continuous phase of styrene/divinylbenzene high internal phase emulsions in the presence of organophilic montmorillonite clay having a novel oil-based intercalant which is a reactive methacryl derivative of quaternized methyl oleate. The morphological features, thermal stability and mechanical properties, namely compression modulus and crush strength of the resulting composites have been investigated as a function of degree of nanoclay loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Until today, many research groups reported polyHIPEs prepared from Pickering HIPEs stabilized by various functionalized solid particles. Some examples are titania , silica , hydroxyapatite nanoparticles , magnetite nanoparticles , water‐dispersible copolymer particles , lignin particles , serum albumin protein nanoparticles , colloidal polymeric particles and clay .…”
Section: Introductionmentioning
confidence: 99%
“…Until today, many research groups reported polyHIPEs prepared from Pickering HIPEs stabilized by various functionalized solid particles. Some examples are titania , silica , hydroxyapatite nanoparticles , magnetite nanoparticles , water‐dispersible copolymer particles , lignin particles , serum albumin protein nanoparticles , colloidal polymeric particles and clay .…”
Section: Introductionmentioning
confidence: 99%
“…Using silica particles as functional reinforcement allows to enhance their mechanical properties [11,15,19e21]. Incorporating other particles, such as carbon nanotubes [22,23], titania [24], nanoclay [25] and magnetic particles [26,27], have also been explored. Emulsion templated poly(styrene-co-divinylbenzene)/polyurethane interpenetrated polymer networks were synthesised by L epine et al [28].…”
Section: Introductionmentioning
confidence: 99%
“…PolyHIPEs were first prepared and patented by the Unilever researchers, Barby and Haq in 1985 from water‐in‐oil (w/o) HIPEs of styrene (St) and divinylbenzene (DVB) . Then, scientists applied several approaches to enhance mechanical properties of polyHIPEs such as by using different monomers that give flexibility and durability to the structure, increasing the crosslinking ratio, adding a suitable reinforcer to continuous phase and increasing the density of material . In this respect, silica nanoparticles, titania nanoparticles, and carbon nanotubes have been used to reinforce different polyHIPE matrices.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Çira et al . prepared polyHIPE/clay composites by using a reactive intercalant and achieved to improve thermal and mechanical properties of the materials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation